Panchayati Raj in Kerala Tortuous Road - Jos Chathukulam (Economic and Political Weekly January 26, 1991, 1991)
After repeated aborted attempts at democratic decentralisation, district councils are about to be constituted in Kerala under the District Administration Act, 1979 which had been kept in cold storage for 12 years.